2013
DOI: 10.5812/traumamon.12450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taping on Pain, Grip Strength and Wrist Extension Force in Patients with Tennis Elbow

Abstract: BackgroundTennis elbow (TE) is a common musculotendinous degenerative disorder of the extensor origin at the lateral humeral epicondyle. Different modes of treatment are used for management of tennis elbow.ObjectivesThis study investigated the effect of the taping technique (TT) on pain, grip strength and wrist extension force in treatment of tennis elbow.Patients and MethodsThirty patients (16 men /14 women with a mean age of 32.2 years) with tennis elbow of their dominant arm participated in this study. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
1
33
2
Order By: Relevance
“…Our findings were in agreement with the previous studies which involving diamond taping for lateral epicondylalgia by Shamsoddini and Hollisaz [10], and Vicenzino et al, [12]. Also, Goel et al, concluded that, athletic tape and KT equally effective in gaining short term benefits in lateral epicondylalgia [11].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings were in agreement with the previous studies which involving diamond taping for lateral epicondylalgia by Shamsoddini and Hollisaz [10], and Vicenzino et al, [12]. Also, Goel et al, concluded that, athletic tape and KT equally effective in gaining short term benefits in lateral epicondylalgia [11].…”
Section: Discussionsupporting
confidence: 83%
“…Patients were excluded if they had dominant hand fracture through the last year, neuromuscular diseases, rheumatoid or degenerative diseases of the dominant hand, any upper-limb neurological abnormalities, allergies to adhesive tape, previous surgery to elbow and/or congenital or acquired deformities of the elbow [10][11][12]. All participants signed a consent form approved by the ethical committee of the Faculty of Physical Therapy, Cairo University, before the beginning of the study.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations